Investigation on Compressive Strength of Opc-Waste Material Geocomposite - Chow, Shiao Huey; Ibrahim, Anas; Abdul Ghani, Abdul Naser (Infrastructure Technology Research Unit, USM, 2007)
This study investigates the compressive strength of cement (OPC) bound waste material geocomposite. Two different waste materials namely tire shred and rubber shred were investigated in this project.